2010
DOI: 10.1001/archinternmed.2010.112
|View full text |Cite
|
Sign up to set email alerts
|

β-Blockers May Reduce Mortality and Risk of Exacerbations in Patients With Chronic Obstructive Pulmonary Disease

Abstract: Treatment with beta-blockers may reduce the risk of exacerbations and improve survival in patients with COPD, possibly as a result of dual cardiopulmonary protective properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
220
1
16

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(253 citation statements)
references
References 38 publications
(66 reference statements)
10
220
1
16
Order By: Relevance
“…Historically, β-blockers are not recommended because of potential respiratory adverse effects; blocking β 2 -adrenoceptors could lead to broncho constriction and worsening lung function. Evidence suggests that β 1 -selective blockers are generally well-tolerated in patients with chronic obstructive pulmonary disease and might improve survival and, paradoxically, bronchial responsiveness 85 . Given its high β 1 -selectivity, bisoprolol is the only β-blocker that is not contraindicated in chronic obstructive pulmonary disease.…”
Section: Myocardial Ischaemiamentioning
confidence: 99%
“…Historically, β-blockers are not recommended because of potential respiratory adverse effects; blocking β 2 -adrenoceptors could lead to broncho constriction and worsening lung function. Evidence suggests that β 1 -selective blockers are generally well-tolerated in patients with chronic obstructive pulmonary disease and might improve survival and, paradoxically, bronchial responsiveness 85 . Given its high β 1 -selectivity, bisoprolol is the only β-blocker that is not contraindicated in chronic obstructive pulmonary disease.…”
Section: Myocardial Ischaemiamentioning
confidence: 99%
“…Such agents should not, therefore, be withheld from COPD patients if there is an appropriate indication [31]. Indeed, there is emerging evidence that there may be some benefit of b-blockers in COPD outside of the context of cardiovascular disease [32], although as yet, this is far from established.…”
Section: Ischemic Heart Diseasementioning
confidence: 99%
“…[13][14][15][16][17] Finally, epidemiological studies and meta-analyses clearly demonstrated in non-selected COPD populations (with or without heart diseases) that BB treatment decreased mortality and acute exacerbations of COPD. [1][2][3][17][18][19][20] The possible mechanisms of the beneficial effects (cardioprotection mainly) of BB in the setting of COPD include: the presence of subclinical heart disease (ischemic heart disease, heart failure, arrhythmias etc. ), 5 the presence of clinically manifest heart disease, 10 the attenuation of cardiovascular side effects of beta-agonist medication, 11 and the correction of bronchial beta2-receptor down-regulation induced by beta-agonists.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, one of the observations regarding BB treatment was its -seemingly paradoxical -beneficial effect in case of chronic obstructive pulmonary disease (COPD). [1][2][3] This may imply changing the current paradigm, which consists in a relative contraindication of BB in COPD, due to the fact that they may cause bronchospasm.…”
Section: Introductionmentioning
confidence: 99%